Drug Solubility Enhancement Strategies Using Amorphous Solid Dispersion: Examination on Type and The Amount of the Polymer - Seftian, Muhammad; Laksitorini, Marlyn Dian; Sulaiman, Teuku Nanda Saifullah (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Solubility is one of the critical factors affecting the biopharmaceutical process of drugs. Low solubility limits the dissolution rate and the oral bioavailability. As a result, a higher drug load is required to compensate for the low bioavailability. Amorphous solid dispersion (ASD) is a recent approach to increase drug solubility by dispersing the drug in a carrier-commonly a hydrophilic polymer. It improves the solubility and dissolution rate by affecting the thermodynamic equilibrium of the drug in solution. The amorphous system has a random molecular arrangement leading to higher thermodynamic activity. The amorphous system in ASD has a higher free energy which facilitates a higher solubility and dissolution rate. Polymer is the main component after the active substance in the ASD system. Therefore, the success of ASD formulation will be determined by the selection of polymers and additives as well as their proportions in the system. In addition to the polymer, surfactants are used as a ternary system to give a synergistic effect on the dissolution rate. The system maintains drug supersaturation in the solution state through two main mechanisms: reducing molecular mobility and plasticizing effect.